Diagnostic yield of standardized screening for deep venous thrombosis in patients with acute cerebral ischemia and cardiac right-to-left shunt - K.M. Michael; L.P. Pallesen; D.P.O. Kaiser; T. Siepmann; J. Barlinn; A. Sedghi; N. Weiss; M. Weise; S. Werth; K. Barlinn; Volker Puetz (Neurological Research and Practice)
Abstract Background Paradoxical embolism is a potential pathophysiology in patients with acute ischemic stroke or transient ischemic attack (TIA) and patent foramen ovale (PFO) or atrial septal defect (ASD). We sought to determine the frequency of deep vein thrombosis (DVT) detection by standardized lower extremity venous compression ultrasound (LE-CUS) in patients with acute cerebral ischemia and cardiac right-to left shunt due to PFO or ASD on transoesophageal echocardiogram (TEE). Methods We analysed consecutive patients (01/2015-12/2020) with acute cerebral ischemia and PFO or ASD on TEE, who received DVT screening by LE-CUS per institutional standard. We determined clinical baseline variables including shunt-size categorized as small, medium or large, and analysed the frequency of DVT. We performed multivariable analysis to identify predictors for presence of DVT on LE-CUS. Results Among 1564 patients with acute ischemic stroke (n = 1326) or TIA (n = 238) who received TEE, 390 patients had PFO and 10 patients ASD, of whom 274 were screened for DVT by LE-CUS (153 [55.8%] female, age 64 years [51–76], NIHSS score 4 [1-9.5]). Of these, 55 patients (20.1%) had DVT on LE-CUS. Among patients with DVT, 23 of 76 patients (30.3%) who received LE-CUS within 72 h from admission compared to 32 of 198 patients (16.2%) who received LE-CUS at later time points had presence of DVT (p = 0.012). The percentage of patients with DVT tended to be higher among patients with cryptogenic ischemic stroke compared to patients with other stroke etiologies (21.8% [49 of 225] vs. 12.2% [6 of 49]; p = 0.168). Presence of DVT was associated with female sex (OR 2.24, 95%CI 1.09–4.62), NIHSS score (OR 1.06, 95%CI 1.03–1.10), Wells score (OR 1.54, 95%CI 1.11–2.13) and shunt size (OR 3.32, 95%CI 1.86–5.91). Conclusions Our data suggest a high diagnostic yield (> 20%) of standardized screening for DVT with LE-CUS in patients with acute cerebral ischemia and PFO or ASD. This particularly applies to females, patients with more severe baseline deficits and large right-to-left shunt. These findings may not be generalizable to all patients with PFO or ASD and need prospective validation.